Program Edukasi Digitalisasi UMKM dalam Rangka Meningkatkan Pemahaman Masyarakat terhadap UMKM yang Berbasis Digital - Yusi Srihartini; Rio Kartika Supriyatna; Evi Novita; Ijlaludin Ijlaludin; Karisma Karisma; Asep Irawan; Ahdatusariroh Ahdatusariroh; Nurul Mariyam (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in strengthening the local economy, including in Gunung Bunder 1 Village, RW 05, which is known for its agricultural potential. However, MSME actors still face several challenges, such as low digital literacy, lack of product innovation, and reliance on traditional marketing methods. This study aims to enhance community understanding of digital marketing, provide assistance in developing processed agricultural products, and encourage the competitiveness of local MSMEs in the digital era. The research method used is qualitative, employing field surveys, interviews with community leaders, and secondary data analysis. The empowerment program was implemented through MSME digitalization seminars, interactive discussions, and practical training such as creating online business accounts and conducting social media-based promotions. The results indicate an increased awareness among MSME actors regarding branding, digital marketing strategies, and product innovation. This activity is expected to serve as an initial step in transforming village MSMEs to become more innovative, competitive, and capable of optimizing local potential for community welfare.